Pendidikan Islam Prespektif Syeikh Nawawi Al–Bantani dan Relevansinya di Era Modern - Wiyanto, Harry (MAN 1 Kota Kediri, 2024)
Sheikh Nawawi Al-Bantani's thoughts regarding Islamic education emphasise tarbiyah, ta'lim and ta'dib and knowledge transfer. According to him, Islamic education emphasizes the principles of Islamic education: 1) Presenting subjects starting from the easy, concrete ones that students' minds can grasp, then gradually brought to more difficult and abstract ones. 2) In delivering material, teachers have to consider the condition of the students, especially in terms of abilities and typology. 3) Use appropriate teaching methods with the condition of the students. 4) In delivering material teachers do not add new material before the students understand the previous ones because of this they can be the perfect human. 5) The principle of repetition (krar) in teaching. Sheikh Nawawi Al Bantani's thoughts on relating Islamic education with the modern world. Keywords: Islamic Education, Sheikh Nawawi Al Bantani, Modern era